Can digital rights management be standardized?. - Rump, N. (IEEE Signal processing magazine)
With increasing use of the Internet as a content-distribution platform, mere interoperability of the codec is no longer sufficient if content owners are not prepared to distribute their content online for fear of piracy. Therefore, one also needs interoperability in the area of managing and protecting related intellectual property rights. To provide interoperability of digital rights management (DRM) systems to protect the content rather than the distribution channel, MPEG has embarked on developing intellectual property management and protection (IPMP) specifications targeted at the content itself that are natively built into its standards. It is the hope that such standards will allow for interoperability of content commerce systems, giving consumers more choice, while providing rights holders with the tools to effectively protect their assets and to develop complex and attractive business offering to tempt consumers. While it remains uncertain whether standardization is in fact the right vehicle to provide the e-content market with an impetus to grow, it appears that MPEG is working on a set of specifications with relatively good chances of helping to achieve this goal.